Determinant of Employee Performance and Employee Productivity on Sector Travel Company - putra, Juniawan mandala; Murdiono, Jatmiko; Susilowati, Tri; Nuraeni, Nuraeni; AR, Muchdir (The Eastasouth Management and Business, 2024)
This article aims to dig deeper into the determinants of employee performance and employee productivity in the travel company sector in a literature review with the following contributions. This article uses qualitative methods, where literature reviews related to related topics and research objects in this paper describe the findings of the results and then given a perspective from the final results of this article. Article sources come from international journals with a time scale of one year. In this article, the purpose of the study to find a literature relationship between employee performance variables and employee productivity is with notes for the object of research in the field of travel is not found specifically for the two variables. For the direct relationship between these two variables, there is a direct and significant influence in various fields as presented in this article.